Determination of the Scarcity Index in the "Hoya Oscura" Stream Micro-Basin, Municipality of Pamplona, Norte de Santander (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2014)
This article presents the research project carried out in the "La Hoya Oscura" stream micro-basin, in the municipality of Pamplona, during the months of October, November, and December 2012, whose objective was to determine the scarcity index of the micro-basin under study. To achieve this, information was collected through a survey applied to the community in the study area to establish the number of inhabitants, the number of animals, water resource uses, types of crops, etc. Additionally, data collection was carried out through a field visit, using instruments such as a GARMIN ETREX 20 GPS, Google Earth, AutoCAD Civil 3D 2011, and MapSource to perform the mapping of the basin.